Sex difference in developmental changes in visualized Kiss1 neurons in newly generated Kiss1-Cre rats - Koki YAMADA; Mayuko NAGAE; Tetsuya MANO; Hitomi TSUCHIDA; Safiullah HAZIM; Teppei GOTO; Makoto SANBO; Masumi HIRABAYASHI; Naoko INOUE; Yoshihisa UENOYAMA; Hiroko TSUKAMURA (The Society for Reproduction and Development, 2023)
Hypothalamic kisspeptin neurons are master regulators of mammalian reproduction via direct stimulation of gonadotropin-releasing hormone and consequent gonadotropin release. Here, we generated novel Kiss1 (kisspeptin gene)-Cre rats and investigated the developmental changes and sex differences in visualized Kiss1 neurons of Kiss1-Cre-activated tdTomato reporter rats. First, we validated Kiss1-Cre rats by generating Kiss1-expressing cell-specific Kiss1 knockout (Kiss1-KpKO) rats, which were obtained by crossing the current Kiss1-Cre rats with Kiss1-floxed rats. The resulting male Kiss1-KpKO rats lacked Kiss1 expression in the brain and exhibited hypogonadotropic hypogonadism, similar to the hypogonadal phenotype of global Kiss1 KO rats. Histological analysis of Kiss1 neurons in Kiss1-Cre-activated tdTomato reporter rats revealed that tdTomato signals in the anteroventral periventricular nucleus (AVPV) and arcuate nucleus (ARC) were not affected by estrogen, and that tdTomato signals in the ARC, AVPV, and medial amygdala (MeA) were sexually dimorphic. Notably, neonatal AVPV tdTomato signals were detected only in males, but a larger number of tdTomato-expressing cells were detected in the AVPV and ARC, and a smaller number of cells in the MeA was detected in females than in males at postpuberty. These findings suggest that Kiss1-visualized rats can be used to examine the effect of estrogen feedback mechanisms on Kiss1 expression in the AVPV and ARC. Moreover, the Kiss1-Cre and Kiss1-visualized rats could be valuable tools for further detailed analyses of sexual differentiation in the brain and the physiological role of kisspeptin neurons across the brain in rats.